Theoretical and experimental investigation of diesel engine with steam injection system on performance and emission parameters - Kokkulunk, Gorkem; Gonca, Guven; Ayhan, Vezir; Cesur, Idris; Parlak, Adnan (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
In the present study, a new electronically controlled steam injection method is applied to a direct injection (DI) diesel engine to control NOx emissions. This method can be also used to improve the performance and efficiency. Steam injected diesel engine is modeled by using zero-dimensional single-zone combustion model for 20% steam ratio at full load condition. The obtained results are compared with conventional diesel engine in terms of performance and NO, CO, CO2, HC emissions. The simulation results agree with experimental data quite well. In the experimental results, it is determined that the engine torque and the effective power increase up to 2.5% at 1200 rpm, specific fuel consumption (SFC) and effective efficiency improves up to 6.1% at 2400 rpm, NO emissions reduce up to 22.4% at 1200 rpm, CO2 emissions decrease up to 4.3% at 1800 rpm, smoke density increases from 44% to 46% at 2200 rpm. This paper may be a leading essential tool for the real-engine designers by considering the effects of steam injection into the engine cylinder. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Diesel engine; Steam; Emissions; Single-zone combustion model; Performance; EMULSIFIED DIESEL; FUEL; COMBUSTION; EMULSIONS; NOX; PREDICTION; Thermodynamics; Energy & Fuels; Engineering; Mechanics